Pemilihan Platform E-Commerce Menggunakan Ahp Pada Apotek Djapuri Farma2 - Irawan, Made; Susanto, Erliyan Redy; Puspaningrum, Ajeng Savitri; Neneng, N; Ulum, Faruk (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This study explores the selection of the optimal e-commerce platform for Djapuri Farma2 Pharmacy using the Analytic Hierarchy Process (AHP) method. In this context, the five main criteria considered are Cost, Security, Completeness of Features, Ease of Use, and Community Support. The AHP method is used to carry out pairwise comparisons between available alternative e-commerce platforms. After going through an evaluation process, WooCommerce was chosen as the platform that best suited the pharmacy's needs. The novelty of this research lies in the application of the AHP method in the specific context of the pharmaceutical industry, which has not been widely discussed in previous literature. By focusing on criteria relevant to pharmacies, this study provides a new contribution to the e-commerce platform selection literature with an approach that can be directly applied in the healthcare industry. Opportunities for future research development include expanding evaluation criteria, such as including sustainability factors, as well as combining AHP with other methods such as TOPSIS or ANP to obtain more comprehensive and robust results. This study is expected to become an important reference for other pharmacies who want to carry out digital transformation through choosing the right e-commerce platform.